Aumolertinib Effectively Reduces Clinical Symptoms of an EGFR L858R-Mutant Non-Small Cell Lung Cancer Case Coupled With Osimertinib-Induced Cardiotoxicity: Case Report and Review - Zhang, Qianqian; Liu, Haiyang; Yang, Jia (Frontiers in Endocrinology, 2022)
Osimertinib a third-generation epidermal growth factor receptor tyrosine kinase inhibitor (EGFR-TKI) firstline therapy has shown good clinical outcomes in NSCLC, but some serious adverse events include cardiotoxicity have also been reported. Here, we present the first NSCLC case with osimertinib induced cardiac failure. The case is successfully being treated by switching to another third-generation TKI, aumolertinib. A 62-year-old non-smoker woman initially diagnosed with stage cT2aN2M1c IVB non-small-cell lung cancer (NSCLC) with synchronous brain and bone metastasis in April, 2020. Further genetic screening of the patient identified Leu858Arg(L858R) mutation in EGFR thus the patient was administered third-generation TKI osimertinib (80 mg per day) for 6 months. This treatment of osimertinib led to serious cardiac failure but no significant reduction in NSCLC tumor size. To cope with these conditions, another third-generation TKI aumolertinib (110 mg per day) along with a supplement treatment plan was prescribed to the patient. Interestingly, this new treatment plan of aumolertinib significantly inhibited the tumor growth in 8 months. Therefore, we conclude that the administration of second-line aumolertinib 110 mg/day, has fewer adverse reactions and high efficacy against NSCLC as compared to osimertinib therapy.